Studi Biblika dan Reflektif : Mazmur 121 “Sebuah Perjalanan Hidup Mengikut Tuhan” - Putra, Luke Eka (Diligentia: Journal of Theology and Christian Education, 2026)
This paper examines Psalm 121:1–2 from both a biblical and reflective perspective by understanding life as a journey of faith, rather than a pursuit of specific achievements. Starting from the reality of human life—filled with challenges, struggles, and uncertainties—Psalm 121 is read within the context of the Songs of Ascents (Psalms 120–134) as a series of hope-filled songs of God’s people who are journeying toward Jerusalem. This study explores the historical and geographical background of Israel’s pilgrimage, which was fraught with risks and threats, thus shaping a theological metaphor of total dependence on God. A lexical analysis of the verb “to lift up one’s eyes” (נָשָׂא, nāśāʾ) compared with the verb “to see” (רָאָה, rāʾāh) in the narratives of Genesis and Samuel shows a shift in meaning: from a type of seeing that leads to sin to a seeing of faith directed toward God. Furthermore, an examination of the word “help” (עֵזֶר, ʿēzer) affirms that the help from the Lord in Psalm 121 is not merely temporary assistance, but rather God’s active and eternal accompaniment as Creator. The paper concludes with a theological reflection relevant to modern life, emphasizing that in a journey filled with spiritual crises, believers are called to direct their gaze and hope solely toward the Lord, the Maker of Heaven and Earth.